Sound treated room in a speech and hearing clinic - SS, Murthy; KT, Jacob (Journal of All India Institute of Speech and Hearing, 1970)
Aucostic environment plays an important role in the field of Audiology and Speech Pathology especially in conducting hearing acuity tests. A suitable aucostic environment is required to carry out free-field tests especially for children and for recording the speech samples of patients with defective speech before, during and after therapy. For the above test requirements, the Speech and Hearing Clinic should be provided with a satisfactory sound treated room